ANALISIS PEMAHAMAN SISWA DALAM MENYUSUN LAPORAN KEUANGAN PADA MATA PELAJARAN EKONOMI KELAS XI DI SMA SRIGUNA PALEMBANG TAHUN PELAJARAN 2013/2014 - Zahruddin Hodsay; Lia Oktasari (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2014)
The financial statements are written reports that provide information on the company's financial statements for a certain period. The problem in this study is "how is the understanding of students in preparing financial statements on economic subjects in SMA Sriguna Palembang year lesson 2013/2014?". The purpose of this study to determine the understanding of students in preparing financial statements on economic subjects in SMA Sriguna Palembang year lesson 2013/2014. The research method used is descriptive quantitative method. The population of the study were students of class XI IPS of 119 people. Determination of sample with siinpel random sampling that class XI IPS 1 and XI IPS 3 which amounted to 79 people. This data collection is done by documentation and test techniques. From the analysis of data can be seen that the results of students who understand 49 students with a percentage of 62.03%, students who get the value with the category of understand a number of 18 students with a percentage of 22.78%, students who get the value with the category enough to understand a number of 4 people with a percentage of 8.86%, while students who scored under the category of less than 4 people with a percentage of 5.07% and students who scored in categories not understood amounted to 1 person with a percentage of 1.26%. Based on the research result, it is concluded that the average of the students 'understanding of class XI IPS SMA Sriguna Palembang in preparing the financial statements in the subjects of economics year 2013/2014 of 85.02%, the researcher concludes that the students' understanding in completing the financial statements of accounting services company in SMA Sriguna Palembang belongs to the Understanding category.